2023
DOI: 10.56553/popets-2023-0072
|View full text |Cite
|
Sign up to set email alerts
|

Lessons in VCR Repair: Compliance of Android App Developers with the California Consumer Privacy Act (CCPA)

Abstract: The California Consumer Privacy Act (CCPA) provides California residents with a range of enhanced privacy protections and rights. Our research investigated the extent to which Android app developers comply with the provisions of the CCPA that require them to provide consumers with accurate privacy notices and respond to "verifiable consumer requests" (VCRs) by disclosing personal information that they have collected, used, or shared about consumers for a business or commercial purpose. We compared the actual n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…Chen et al [9] focused on the right to know and showed that even if websites are legally required under the CCPA to disclose certain data practices, variance and vagueness in definitions can lead to confusion among users. Samarin et al [28] issued access requests to mobile apps and compared the results to personal data observed through a analysis of app network traffic; they found that significant percentages of apps collected personal information that was not disclosed when users invoked their right to know.…”
Section: Related Workmentioning
confidence: 99%
“…Chen et al [9] focused on the right to know and showed that even if websites are legally required under the CCPA to disclose certain data practices, variance and vagueness in definitions can lead to confusion among users. Samarin et al [28] issued access requests to mobile apps and compared the results to personal data observed through a analysis of app network traffic; they found that significant percentages of apps collected personal information that was not disclosed when users invoked their right to know.…”
Section: Related Workmentioning
confidence: 99%